Spherical layout for 3D graph visualization - Larrea, Martin Leonardo (2007)
Information Visualization is a field of research that has less than ten years of history, but has growing very fast as a reach and interdisciplinary research field. The last advances in Visualization and, particularly in Information Visualization, also highlights fundamental research issues. Nowadays, it is currently a challenging task for designers to find out the strategies and tools available to visualize a particular type of information.